Green entrepreneur handbook : the guide to building and growing a green and clean business - Koester, Eric (What every engineer should know, 2011)
The first section of the book lays the groundwork for any new entrepreneur to understand the history of the environmental and clean technology movements. The next section takes a new business from initial idea to sales of the product or service. Emphasizing aspects unique to the green business environment, the third part provides a sound understanding of energy generation and distribution, addresses regulatory